Shift work is significantly and positively associated with possible gastro-esophageal reflux disease: A meta-analysis study - Hsiang-Tai Chen; Hung-Yi Chuang; Hung-Yi Chuang; Tsung-Yu Hsieh; Pei-Shan Wu; Fang-Jiun Lin; Huan-Chih Huang; Chen-Cheng Yang; Chen-Cheng Yang; Chen-Cheng Yang; Chao-Hung Kuo (Frontiers Media S.A., 2022)
BackgroundOne of the health issues related to shift work patterns is possible gastro-esophageal reflux disease (GERD) symptoms. However, the association between shift work and possible GERD symptoms through meta-analysis has not been developed in the current literature field. Therefore, the purpose of this study is to analyze the association between shift work and possible GERD symptoms through meta-analysis.MethodsStudies containing target keywords were found in three datasets, and four articles were selected for further analysis after examining the title, abstract, and text. All prevalence odds ratios (ORs) among different groups of the population and the standard error (SE) from each included study were calculated for conducting meta-analysis.ResultThe pooled OR has shown a significant positive association between shift work and possible GERD (OR 1.53; 95% confidence interval [CI] 1.33-1.77, p-value 0.003). Compared to non-shift workers, the subgroup analysis indicates there are positive associations between possible GERD and the night shift (OR 1.39; 95% CI 1.16-1.66), and the rotating shift (OR 1.83; 95% CI 1.44-2.33). The subgroup analysis has also shown similar trends in shift working men (OR 1.28; 95% CI 1.03-1.60) and shift workers of both genders (OR 1.75; 95% CI 1.45-2.11).ConclusionThis study has shown a positive association between shift work and possible GERD.